2005
DOI: 10.1016/j.ymthe.2005.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of Immune Responses to Introduced Human Acid α-Glucosidase by Liver-Restricted Expression in Glycogen Storage Disease Type II

Abstract: Glycogen storage disease type II (GSD-II; Pompe disease) is caused by a deficiency of acid alpha-glucosidase (GAA; acid maltase) and manifests as muscle weakness, hypertrophic cardiomyopathy, and respiratory failure. Adeno-associated virus vectors containing either a liver-specific promoter (LSP) (AAV-LSPhGAApA) or a hybrid CB promoter (AAV-CBhGAApA) to drive human GAA expression were pseudotyped as AAV8 and administered to immunocompetent GAA-knockout mice. Secreted hGAA was detectable in plasma between 1 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
195
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(207 citation statements)
references
References 43 publications
9
195
1
Order By: Relevance
“…Studies demonstrate that expression of the acid alpha glucosidase gene within muscle cells or in some cases secretion of GAA from liver leads to a reduction of the glycogen storage abnormality in the mice. Moreover, these studies showed that the immune response to the expressed enzyme in AAV-treated Pompe mice treated can be reduced in some cases117,121 or be influenced by tissue specific expression 118,119…”
Section: Enzyme Replacement and Other Emerging Therapiesmentioning
confidence: 99%
“…Studies demonstrate that expression of the acid alpha glucosidase gene within muscle cells or in some cases secretion of GAA from liver leads to a reduction of the glycogen storage abnormality in the mice. Moreover, these studies showed that the immune response to the expressed enzyme in AAV-treated Pompe mice treated can be reduced in some cases117,121 or be influenced by tissue specific expression 118,119…”
Section: Enzyme Replacement and Other Emerging Therapiesmentioning
confidence: 99%
“…Therefore, responses are generally dose dependent 43 and can be avoided by a more restricted expression, for example by using tissuespecific promoters as opposed to systemic general promoters. [44][45][46] Independent from these findings, evidence is accumulating that targeting AAV vectors specifically to the liver seems to induce tolerance to the transgene product. 13,47,48 Tolerance induction in liver: the role of regulatory T cells…”
Section: Immunity To the Encoded Transgenementioning
confidence: 99%
“…34 TfR2 and HFE are capable of forming a complex, 35,36 suggesting that the complex is involved in hepcidin regulation. 37 In this study, we used a recombinant serotype 2 adenoassociated virus vector pseudotyped with serotype 8 capsid (AAV2/8) and carrying a hepatic-specific promoter 38 to express either Hfe or Tfr2 in mice to test the role of the HFE/TfR2 complex in the regulation of hepcidin. Our results indicate that the virally encoded Hfe and Tfr2 are expressed in mouse livers.…”
Section: Introductionmentioning
confidence: 99%